(untitled) (Ciencias de la Ingeniería y Aplicadas, 2021)
The present investigation was carried out for a radio media outlet, where the procedure applied for the live transmission of radio content was observed; The information is processed manually and with unsuitable means for storage, causing loss of time, rudimentary control of musical programming, news, commercial spots, among others. Through frequent interviews with the representative and collaborators of the media, the request for requirements for the development of the application was made using technological tools adjusted to the conditions of the case to be solved. The stated objective was achieved, the mobile application with web administration has been approved by the sponsoring users and is currently in operation.